2017
DOI: 10.3233/jad-170339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study

Abstract: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
5
0
5
Order By: Relevance
“…Most studies have explored delirium in the hospital setting and almost always in older individuals (e.g., > 65 years), rather than in the general population [5]. While relatively uncommon in the outpatient setting [6], delirium affects nearly 20% of patients over age 75 on medical inpatient units when formally assessed by experienced clinicians [7]. In intensive care unit (ICU) settings the prevalence is significantly higher, where rates of over 80% have been reported in mechanically ventilated patients [8].…”
Section: Epidemiology Incidence and Prevalence Of Deliriummentioning
confidence: 99%
“…Most studies have explored delirium in the hospital setting and almost always in older individuals (e.g., > 65 years), rather than in the general population [5]. While relatively uncommon in the outpatient setting [6], delirium affects nearly 20% of patients over age 75 on medical inpatient units when formally assessed by experienced clinicians [7]. In intensive care unit (ICU) settings the prevalence is significantly higher, where rates of over 80% have been reported in mechanically ventilated patients [8].…”
Section: Epidemiology Incidence and Prevalence Of Deliriummentioning
confidence: 99%
“…Delirium is also common in nursing home residents and in postacute settings, with a prevalence ranging from 1.4 to 70.3% [5], and between 13 and 26%, respectively [6, 7]. The presence of delirium at home is relatively low with a prevalence ranging from 1 to 2% [4, 8]; though a recent study has reported a prevalence as high as 13% in an outpatients memory clinic [9]. However, few studies have addressed delirium epidemiology outside the hospital thus limiting our ability to provide detailed information of delirium prevalence in other settings.…”
Section: Introductionmentioning
confidence: 99%
“…Os subtipos mistos e hipoativos são os mais prevalentes em ambiente hospitalar 9 e também aqueles com pior prognóstico 11 . Na APS, a maioria manifesta-se como delirium hiperativo 10,16 , já que são normalmente pacientes com patologia menos grave e fisicamente mais capazes de manifestar agitação psicomotora 10,17 .…”
Section: Características Clínicas E Subtipos De Deliriumunclassified
“…A possibilidade de existência de delirium deve ser considerada em todas as consultas de rotina de pacientes com demência ou idade avançada, principalmente naqueles que tiverem internamento recente, já que mais de metade dos diagnósticos de delirium detetados na APS está associada a hospitalização recente 17 .…”
Section: Diagnósticounclassified